Religion and war from antiquity to early modernity - Polinskaya, Irene; James, Alan 1965-; Papadogiannakis, Yannis (Bloomsbury Academic, 2024)
"Responding to the profound challenges of our times, this book provides a comparativeand cross-cultural exploration of the role of religion in war in a long historicalperspective, from the second millennium BCE, and even earlier, up to early modernity. Individual chapters focus on the ancient Near East, the Mediterranean basin, Europe and North Africa. Widely diverse case studies explore the historic link between the conduct of war and the growing complexity of human society conditioned by the ownership of ideological authority. The book explores how in most historical societies this authority was religious. Written by experts from different disciplinary perspectives, the volume challenges common assumptions about the historical relationship between religion and war and extends our understanding of the dangers and complexities of today’s world."
Keywords: War / Religious aspects; Religion and politics / History; Konferenzschrift